Identification and prioritization of population health indices in Iranian population, a qualitative study - Mahshid Roohravan Benis; Zahra Rampisheh; Nogol Motamed-Gorji; Mahnaz Solhi; Batool Tayefi (BMC Public Health)
Abstract Introduction A population health index is a combination of two or more health indicators, used to evaluate different dimensions of health in a population. While various population health indices have been developed globally, there remains a gap in systematically identifying and prioritizing such indices tailored to the Iranian context. This study aims to identify and prioritize population health indices relevant to the Iranian context using expert consensus through the Delphi method. Methodology A multi-methodology with two steps was employed in this study. Firstly, a comprehensive list of existing composite health indicators was identified by reviewing the literature. In the second stage, the review results were used as input for a web-based Delphi survey involving 22 experts across two rounds. After two rounds, a list of indices that gained at least 70% of consensus and a mean score of 2.5 out of 5 was prepared. Results In the initial phase of the study, a refined set of 21 indices emerged. Participation rates for the first and second rounds were 72% and 68%, respectively. A total of 21 indices were assessed, and after refining them based on expert feedback, the following five indices were determined to have the highest priority after two rounds: Disability-Adjusted Life Year (4.23 ± 0.32), UHC Service Coverage index (3.96 ± 0.25), Sustainable Development Goals index (3.78 ± 0.31), Human Development Index (3.58 ± 0.36), Quality-Adjusted Life Year (3.58 ± 0.37). The Inter-rater reliability test found significant absolute agreement among experts in the second round (ICC: 0.970, 95% CI: 0.931–0.989). Conclusion This study’s contribution lies in offering a compilation of composite health indicators, which can guide forthcoming research on the health measurement of the Iranian population. Furthermore, the study underscores the value of involving expert professionals and soliciting diverse perspectives in selecting health indices.